Student Affairs Management In Pesantren-Based Formal Madrasah - Baqiyatush Sholihah (Almarhalah | Jurnal Pendidikan Islam, 2020)
This research studied about student affairs management in Madrasah Aliyah Tajul Ulum as pesantren-based formal madrasah before the madrasah was divided into two for boys and girls (banin and banat). Management aspects here are planning, organizing, staffing, leading, and evaluating. Student affairs scopes are admission of students, orientation of new students, counseling services for students, extra-curricular and co-curricular, development of superior achievement, and tracking of alumnus. This study used qualitative method. The data gained through some techniques, they are interview, observation, and documentation. Interview was done with prominent figures such as principal, vice-principal, staffs that handle student activities, and the managers of pesantren (pengurus pondok). Those techniques are aimed to gain information to answer the research questions. First question: how is the student affairs management in Madrasah Aliyah Tajul Ulum as pesantren-based formal madrasah, the second: what are the supporting and inhibiting factors of student affairs management in Madrasah Aliyah Tajul Ulum. Based on the research, could be concluded that MATU has applied the management functions in admission of students, orientation of new students, counseling services for students, extra-curricular and co-curricular, development of superior achievement, but there is a big lack in the matter of tracking of alumnus, there is no adequate management related to alumnus. Even the supporting factors in student affairs management over there are: attractive environmental condition because there are many pesantrens among the madrasah, cooperative society among the madrasah, cooperative pesantren parties, madrasah’s human resources that almost have educational back-ground of pesantren. Inhibiting factors: lack of fund, the economic level of students’ parents, inadequate number of classrooms, the diversity of students’ backgrounds, shortage of administrative staffs which affects student management.